2010
DOI: 10.2147/copd.s11975
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac injury in patients with COPD presenting with dyspnea: a pilot study

Abstract: Purpose:The aim of this pilot study was to test the hypothesis that myocardial ischemia complicates the management of some patients with chest-pain-free chronic obstructive pulmonary disease (COPD) exacerbations. Methods: In this prospective, observational, cohort study, patients admitted to a 350-bed community teaching hospital, with dyspnea and a primary diagnosis of COPD exacerbation, were followed for enzymatic and electrocardiographic evidence of myocardial ischemia for the first 24 hours of hospital admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…At baseline, COPD patients have been shown to have higher highly sensitive cTnT than the general population [ 135 ]. Patients who present with AECOPD are often found to have elevated serum troponin [ 136 , 137 ], of which a minority are secondary to an acute coronary syndrome [ 96 , 137 139 ], often in the absence of chest pain [ 140 ]. In those admitted to hospital for an AECOPD, elevated serum troponins are correlated with long-term mortality [ 83 , 95 , 138 , 139 ], 30-day mortality [ 85 ], in-hospital mortality [ 142 ], increased length of stay [ 95 , 96 ] and risk of readmission [ 87 ].…”
Section: Markers Of Cardiac Disease In Aecopdmentioning
confidence: 99%
“…At baseline, COPD patients have been shown to have higher highly sensitive cTnT than the general population [ 135 ]. Patients who present with AECOPD are often found to have elevated serum troponin [ 136 , 137 ], of which a minority are secondary to an acute coronary syndrome [ 96 , 137 139 ], often in the absence of chest pain [ 140 ]. In those admitted to hospital for an AECOPD, elevated serum troponins are correlated with long-term mortality [ 83 , 95 , 138 , 139 ], 30-day mortality [ 85 ], in-hospital mortality [ 142 ], increased length of stay [ 95 , 96 ] and risk of readmission [ 87 ].…”
Section: Markers Of Cardiac Disease In Aecopdmentioning
confidence: 99%
“… 4 In addition, a recent study demonstrated that COPD exacerbations (ECOPD) more than double the risk of myocardial infarction in the subsequent 5 days. 5 Subclinical ischaemic events and cardiac arrest occur more frequently after an exacerbation 6 and cardiac events are strong predictors of mortality in this setting. 7 In patients hospitalised with an ECOPD in Waikato, New Zealand, 8 elevated cardiac biomarkers were associated with a 15-times greater likelihood of dying within 30 days of admission than those without raised biomarkers and an 88% total mortality at 5 years.…”
Section: Introductionmentioning
confidence: 99%